Mango pest under attack - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A parasitic wasp is coming to the aid of mango farmers in West Africa, where the mango mealybug has become a pest. The mealybug was first considered serious in Ghana and Togo some seven years ago and then infestations began to occur in Benin,...